Polycystic Kidneys and GM2 Gangliosidosis-Like Disease in Neonatal Springboks (Antidorcas marsupialis). (May 2015) - Herder, V.; Kummrow, M.; Leeb, T.; Sewell, A. C.; Hansmann, F.; Lehmbecker, A.; Wohlsein, P.; Baumgärtner, W.
Clinical, gross, histopathologic, electron microscopic findings and enzymatic analysis of 4 captive, juvenile springboks ( Antidorcas marsupialis ) showing both polycystic kidneys and a storage disease are described. Springbok offspring (4 of 34; 12%) were affected by either one or both disorders in a German zoo within a period of 5 years (2008–2013). Macroscopic findings included bilaterally severely enlarged kidneys displaying numerous cysts in 4 animals and superior brachygnathism in 2 animals. Histopathologically, kidneys of 4 animals displayed cystic dilation of the renal tubules. In addition, abundant cytoplasmic vacuoles with a diameter ranging from 2 to 10 μm in neurons of the central and peripheral nervous system, hepatocytes, thyroid follicular epithelial cells, pancreatic islets of Langerhans and renal tubular cells were found in 2 springbok neonates indicative of an additional storage disease. Ultrastructurally, round electron-lucent vacuoles, up to 4 μm in diameter, were present in neurons. Enzymatic analysis of liver and kidney tissue of 1 affected springbok revealed a reduced activity of total hexosaminidase (Hex) with relatively increased HexA activity at the same level of total Hex, suggesting a hexosaminidase defect. Pedigree analysis suggested a monogenic autosomal recessive inheritance for both diseases. In summary, related springboks showed 2 different changes resembling both polycystic kidney and a GM2 gangliosidosis similar to the human Sandhoff disease. Whether the simultaneous occurrence of these 2 entities represents an incidental finding or has a genetic link needs to be investigated in future studies.